Synthesis and Growth Stimulant Properties of 2-Acetyl-3,7-dimethyl-5H-thiazolo[3,2-a]pyrimidin-5-one Derivatives - Vergush A. Pivazyan; Emma A. Ghazaryan; Roza S. Shainova; Rafael A. Tamazyan; Armen G. Ayvazyan; Aleksandr P. Yengoyan (Journal of Chemistry, 2017)
A convenient, accessible, and high yield method for preparing of 6-methyl-2-thioxo-2,3-dihydropyrimidin-4(1H)-one (1) by treatment of acetoacetic acid ethyl ester with thiourea in sodium methylate was developed. The alkylation of the latter with 3-chloro-pentane-2,4-dione and further regioselective cyclization of intermediate compound (2) in high yield afforded 2-acetyl-3,7-dimethyl-5H-thiazolo[3,2-a]pyrimidin-5-one (3). The halogenation and some transformations of synthesized thiazolo[3,2-a]pyrimidine (3) due to its ketone group were carried out to obtain the corresponding carboxamide, carbothioamide, sulfonohydrazide, and oxime and its alkylated derivatives (5). At preliminary biological studies the synthesized compounds have shown growth stimulant properties. The activity of four of them was higher than 70%, compared with heteroauxin.